Effect of Microwave Irradiation on the Microstructural Properties of Bivoltine Silk Fibroin Films. (2016) - Mahadevaiah,; Urs, G. Thejas; Byrappa, K.; Somashekar, R.
Abstract: Study on the effect of microwave irradiation on structural and physical properties of bivoltine silk fibroin films were carried out. This characteristic analysis was done using X-Ray Diffraction, FT-IR spectroscopy and SEM imaging. The study reveals that the microwave irradiations on silk film for various dosage intervals enhances the cross-linkage between the silk chains and helps in gaining its structure back. This regeneration of silk fibroin films make them more brittle in nature. Further, such cross-linking isolates the residual lithium ion in the matrix and this is evident by the results of analytical studies carried out.